Antibody-drug conjugates in cancer therapy: applications and future advances - Long, Rou; Zuo, Hanrong; Tang, Guiyang; Zhang, Chaohui; Yue, Xinru; Yang, Jinsai; Luo, Xinyu; Deng, Yuqi; Qiu, Jieya; Li, Jiale; Zuo, Jianhong (Frontiers in Immunology, 2025)
Antibody-Drug Conjugates (ADCs) represent an emerging cancer therapeutic strategy and are becoming increasingly significant in the field of public health. With the evolution of precision oncology, the potential applications of ADCs are being realized more broadly. This review provides an overview of the fundamental molecular design of ADCs, examining how each component—antibody, linker, payload, and coupling chemistry—affects the physicochemical and biological properties of the final product. The paper also discusses novel ADC designs that are in preclinical and early clinical development stages as next-generation cancer therapies. These include bispecific ADCs, Probody-drug conjugate, immunostimulatory ADCs (ISACs), Degrader-Antibody Conjugates (DACs), and Dual-Payload ADCs. Their applications and potential future advancements in cancer therapy are also explored.